How Did Copenhagen Summit Affect the Public and Political Perception of Environmental Risks in France? An Interview and Documentary Analysis Focussing on The Pre and Post Copenhagen Environmental Legislation in The Energy Industry - Calvet, Elise (2010)
Environmental risks perceptions influence greatly the decisions and creations of new laws and programs which aim to reduce the carbon emissions and preserve the earth from the human negative influence. This study analyses the degree of influence of the Copenhagen summit but also of the public, politicians and energy experts’ risks perceptions in France on the creation of such regulations. The results were built through a documentary and interview analysis. The interviews were focussed on the risks perceptions of the three groups: the public the politicians and the energy experts. Fifteen people were interviewed in order to allocate five persons per group. According to the declarations of this sample’s individuals, I have been able to conclude that the French politicians and mayors didn’t perceive the same environmental risks as the French citizens. Indeed, the environmental risks which were mentioned spontaneously showed two trends: the French public worried the most for environmental risks which could affect their health like the water or food safety, whereas the politicians interrogated feared more the natural risks with which they had to deal in their function, like floods or seismicity. It was also very clear that the majority of the French mayors were unable to guess properly the environmental risks which worry the most their electors. In addition, each politician interviewed seemed to feel well informed on the environmental risks in France; however they all thought that the French politic class in general was ill-informed on those risks despite an easy access to information. In this study I also tried to confirm the second hypothesis which stated that the public was, in general, not willing to pay for any mitigation. To do so the public sample was questioned on their opinion about the carbon taxation and their willingness to pay such a tax. Half of the interviewees were willing to pay a tax on their carbon pollutions, but the other half was very reticent to contribute to the mitigation process of the consequences of their CO2 emissions. As regards to the scientific experts specialised in the energy industry, they felt less preoccupied by the nuclear-related risks than the other groups. This difference was conveyed by a variation in intensity while discussing the nuclear power plants and wastes’ risks. The documentary analysis focused on the role of the Copenhagen summit in the creation and discussion of new energy-related legislations or programs. As regard to the little amount of new environmental laws and the absent reference to Copenhagen, this Conference of the Parties had almost no influence on the energy field in France.